Penerapan model pembangkit argumen dengan metode investigasi sains untuk meningkatkan kemampuan berargumentasi siswa pada materi kalor - Pratama, Anggara Bayu; Muslim, Muslim; Suhandi, Andi (WaPFi (Wahana Pendidikan Fisika), 2013)
This research based on the importance of argumentation skill for students. Argumentation skill is one of thinking skill that must be reached by student to fulfill the competence standard of highschool graduate. One of the effort to expand student’s argumentation skills is a learning process that fasilitate students to discuss and argue in a group. Model of generating arguments through science investigation method emphasizes learning activities in order to make students involved in enhancing argumentation skills. The purpose of this research is to get a picture of enhanced argumentation skills and student’s aspect of argumentation as the effect of model of generating arguments through science investigation method applied on heat subject. The method of this research is pre-experiment with pretest and posttest group design. The instruments of the research covered argumentation skills test, observation sheet, and interview. The subjects of the research are 33 10th grade students in a high school at Bandung who were collected by cluster random sampling technique. To see the enhancement of student’s argumentation skills, we used normalized gain as the calculation technique (g). The result of the research showed that the enhancement of argumentation skills is on moderate level. Enhancement of argumentation skills aspects (claim, enclose and anilyze data, make justification, and support) is on moderate level. The conclusion showed that model of generating arguments through science investigation method enhanced student’s argumentation skills.